Neuroanatomical Evidence in Support of the Bilingual Advantage Theory - Olulade, O A; Jamal, N I; Koo, D S; Perfetti, C A; LaSasso, C; Eden, G F (Cerebral cortex (New York, N.Y. 1991), 2016)
The "bilingual advantage" theory stipulates that constant selection and suppression between 2 languages results in enhanced executive control (EC). Behavioral studies of EC in bilinguals have employed wide-ranging tasks and report some conflicting results. To avoid concerns about tasks, we employed a different approach, measuring gray matter volume (GMV) in adult bilinguals, reasoning that any EC-associated benefits should manifest as relatively greater frontal GMV. Indeed, Spanish-English-speaking bilinguals exhibited greater bilateral frontal GMV compared with English-speaking monolinguals. Was this observation attributable to the constant selection and inhibition of 2 spoken languages? To answer this question, we drew on bimodal bilinguals of American Sign Language (ASL) and English who, unlike unimodal bilinguals, can simultaneously use both languages and have been shown not to possess the EC advantage. In this group, there was no greater GMV when compared with monolinguals. Together these results provide neuroanatomical evidence in support of the bilingual advantage theory.